2006
DOI: 10.4310/jdg/1143593129
|View full text |Cite
|
Sign up to set email alerts
|

On stability and the convergence of the Kähler-Ricci flow

Abstract: The normalized Kähler-Ricci flow exists for all times, and converges when the first Chern class is negative or zero [4,35]. However, when the first Chern class is positive, there are very few known cases of convergence. In one complex dimension, Hamilton [19] used entropy estimates to show convergence under the assumption of an initial metric of everywhere positive scalar curvature. This last assumption was removed later by Chow [12]. In higher dimensions, convergence was established only in the case of positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
135
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 101 publications
(139 citation statements)
references
References 29 publications
(32 reference statements)
4
135
0
Order By: Relevance
“…Now we need the following convergence result of a sequence of Kähler metrics, which is well-known in literature (cf. [26], [31]). …”
Section: The Pre-stable Conditionmentioning
confidence: 99%
“…Now we need the following convergence result of a sequence of Kähler metrics, which is well-known in literature (cf. [26], [31]). …”
Section: The Pre-stable Conditionmentioning
confidence: 99%
“…The functionals E k were used by Chen and Tian [ChTi1,ChTi2] to obtain convergence of the normalized Kähler-Ricci flow on Kähler-Einstein manifolds with positive bisectional curvature (see [PhSt4] for a related result). The Mabuchi energy is decreasing along the flow.…”
Section: Introductionmentioning
confidence: 99%
“…So we have shown that there is a sequence of times t i and diffeomorphisms F i such that the metrics F * i ω t i converge smoothly to a Kähler-Einstein metric on (M, J). Then by a theorem of Bando-Mabuchi [BM] the Mabuchi energy M ω has a lower bound, and the arguments in section 2 of [PS2] show that…”
Section: The Main Theoremmentioning
confidence: 99%